2022
DOI: 10.4155/fmc-2022-0031
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin Modulators: Past, Present, and Future Perspectives

Abstract: Sirtuins are NAD+-dependent protein lysine deacylase and mono-ADP ribosylases present in both prokaryotes and eukaryotes. The sirtuin family comprises seven isoforms in mammals, each possessing different subcellular localization and biological functions. Sirtuins have received increasing attention in the past two decades given their pivotal functions in a variety of biological contexts, including cytodifferentiation, transcriptional regulation, cell cycle progression, apoptosis, inflammation, metabolism, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 147 publications
0
26
0
Order By: Relevance
“…1050 Only 23.9% (n = 17) of published RCTs explored the effects of SIRT activators on physiological function. As a well-known SIRT activator, 1051 resveratrol (n = 10, 14.1%) received more attention compared with SRT2104 (n = 7, 9.9%) in these studies. Several RCTs showed that resveratrol supplementation could effectively increase the expression or concentration of SIRT1.…”
Section: Rcts Of Sirt Proteinsmentioning
confidence: 99%
“…1050 Only 23.9% (n = 17) of published RCTs explored the effects of SIRT activators on physiological function. As a well-known SIRT activator, 1051 resveratrol (n = 10, 14.1%) received more attention compared with SRT2104 (n = 7, 9.9%) in these studies. Several RCTs showed that resveratrol supplementation could effectively increase the expression or concentration of SIRT1.…”
Section: Rcts Of Sirt Proteinsmentioning
confidence: 99%
“…During the past 50 years, the involvement of SIRTs in cancer biology has been studied, and the accumulated evidence reveals their regulatory role in several important steps during the development and progression of different tumor types [ 103 , 169 , 170 , 171 , 172 ]. SIRTs are involved in various biological pathways in which they could act as either tumor suppressors or activators, depending on the stage of the disease, the histological type, and the tumor microenvironment [ 173 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of small molecule regulators that target SIRTs has become a topic of intense interest the past 30 years with several hundred articles investigating new molecular targets as possible regulators of sirtuins’ enzymatic activity in normal cells and disease. Unfortunately, translating SIRT regulators from the bench to the clinics, faces absences of selective compounds with favorable pharmacokinetic and pharmacodynamic profiles [ 102 , 103 , 104 , 105 ]. Therefore, only 70 studies and respective agents have passed through the preclinical phase and were finely tested in clinical trials as potential treatment options in coronary disease, COVID-19, neurodegenerative disease, diabetes, kidney disease, and cancer [ 106 ].…”
Section: Sirt Proteins: An Overview Of Structure and Functionmentioning
confidence: 99%
“…Some SIRT family members also possess broad-spectrum protein lysine deacylase, mono-ADP-ribosylase, and lipoamidase activities . Given their ability to catalyze the removal of many PTMs, sirtuins are involved in several biological processes, including DNA damage repair, aging, cell cycle regulation, gene expression, metabolism, longevity, and stress response. It is worth noting that epigenetic and metabolic pathways are tightly interconnected. Indeed, most enzymes that catalyze epigenetic modifications use crucial metabolites as cosubstrates (for example, S -adenosyl methionine, α-ketoglutarate, acetyl- and acyl-CoA, FAD/FADH 2 , and NAD + /NADH) .…”
Section: Introductionmentioning
confidence: 99%